Komposisi Nutrien Sampah Organik Sisa Nasi dan Tulang Ikan Nila serta Pengaruhnya Bagi Pertumbuhan Larva Black Soldier Fly (Hermetia illucens L.) - Albert Abrillian; Dwi Aditiyarini; Kukuh Madyaningrana (Pro-Life, 2023)
Organic waste as a by-product of household activities that are produced continuously is still a major problem in Indonesia. Conventional organic waste management still has weaknesses and limitations. Black soldier fly larvae are decomposers that can be used in organic waste management. This study aims to measure the nutrient levels of organic waste used, such as leftover rice, tilapia bones, or a combination of both and study the use of organic waste for the growth of BSF larvae. The research used 150 BSF larvae aged 12 days with three repeats and four test treatments: T51 feed (control), leftover rice, tilapia bones, and a combination of leftover rice and tilapia bones (50:50). The highest levels of carbohydrates and fats were detected in the remaining rice and tilapia bones, respectively. The type of feed has an impact on the nutrients and growth of BSF larvae. The combination treatment produces larvae with the largest biomass and shortest growth time, on the other hand, a single treatment extends the growth time of larvae with a relatively small biomass. The combination treatment between leftover rice and tilapia bones (50:50) is the best type of feed in supporting the growth of BSF larvae, while single feed treatment is considered inappropriate for the growth of BSF larvae.